The Visegrad countries in the European Union: understanding the identity-solidarity nexus in the context of migration and EU enlargement - Větrovcová, Martina (2021)
The European Union (EU) is often hailed as one of the most successful peace projects in the history of humankind. Indeed, since its inception more than 70 years ago, the EU has made unparalleled contributions to the advancement of peace and reconciliation on the European continent. Despite these successes, the EU integration process faces increasing challenges, including the unprecedented departure of one of its members. Further, one of the greatest tests to European cohesion has proved to be the refugee and migrant crisis, which has revealed fault lines over not only migration but also broader issues of identity, norms, and values. In the wake of this crisis, the Visegrad Group— comprised of Hungary, Poland, Slovakia, and the Czech Republic—presented viewpoints that deviated from those held by most Western European states and EU institutions, thus prompting debates about the emergence of a new East–West divide within Europe. Intrigued by whether the notion of solidarity has a different meaning for those who were present at the birth of the EU as opposed to those who joined more than half a century later, this study strives to uncover the Visegrad countries’ understanding of and approach to European solidarity. Making the case that states’ behavior is a result of varying national characteristics deeply rooted within their national identities, it develops an analytical framework for investigating the nexus between identity and solidarity. Applying this framework to the Visegrad states’ responses to the refugee and migrant crisis and their positions and preferences regarding further enlargement of the EU yields three pivotal conclusions. First, the Visegrad states’ identification with the European project as well as their interpretation of the EU’s norms and values, such as that of solidarity, are contingent upon their respective national identities and historical experiences. Second, the particular composition and interaction of identity elements activated in political discourse can explain varying solidarity profiles among different states as well as possible variances in a single state’s behavior across multiple policy areas. And third, the Visegrad states share a great number of similar identity elements, yet often differ in their manifestation or degree of expression. By taking a more nuanced look at the Visegrad cooperation, this study challenges the widespread impression of the Visegrad Group as a homogeneous bloc. The findings make clear that even the same identity element with a slightly different manifestation can lead to different decisions. At the same time, geographical proximity, cultural similarities, and shared historical experience function as a “magnet” that draws the Visegrad states closer together, unites them in their policy preferences, and ensures the continuation of the Visegrad cooperation. In sum, the present study advances the understanding of the process of European integration and the Visegrad Group’s multifaceted role in it.
Keywords: Europäische Union; Visegrád-Staaten; Mitteleuropa; Hochschulschrift